PENGEMBANGAN PORTOFOLIO BERBASIS KRITERIA UNTUK MENGEVALUASI PEMBELAJARAN DI SEKOLAH DASAR - Indriani, Nur; Putri, Regina; Zulkarnai, Feri; Syafruddin, Syafruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Traditional assessments, like wxam standards, do not alwayas reflect the real potential of students and often cannot measure their understanding in depth. This traditional method of judgment is widely criticied for being over-focused and less encouraging creativity, critical thinking, and problem-solving. Effective assessment methods are needed that must have the ability to measure all aspects of student learning, not just academic grades. The research aims to investigate and develop portfolio-based assessment methods that can be used to evaluate the quality of learning in elementary schools. The research uses qualitative methods with document analysis techniques, data collected from various sources, such as journals, books, and articles relevant to research topics. Research results show that portfolio assessment has several advantages over traditional assessments, such as providing a more comprehensive overview of student knowledge and abilities; increasing student learning motivation and responsibility; improving student self-assessment skills; enhancing communication between students, teachers, and parents; supporting student-centred learning, improving teacher's ability to evaluate and provide feedback, recording student progress over time; and increasing teacher confidence in themselves in their responsibilities. Also, in developing a criterion-based portfolio, the criteria included should be clear, non-partisan, and consistent with the learning objectives and contents of the portfolio. Teachers evaluate all aspects of the student, both cognitive, emotional, and psychomotor.